Does Sustainable Tourism Development Enhance Destination Prosperity?. (June 2022) - Falatoonitoosi, Elham; Schaffer, Vikki; Kerr, Don
Prosperity is one of the five critical areas for Sustainable Development according to the 2030 Agenda. This research develops a prosperity model for a tourism destination and examines stakeholders' perception of the role of sustainable tourism development in enhancing the prosperity. A set of 18 sustainability indicators were used and identified through a hybrid model that combines results from a systematic literature search and four-stage convergent interviews. Results from 171 participants from five different groups of stakeholders revealed that sustainable tourism development enhances the prosperity of the target destination in general. Sustainability was found to be a medium to strong predictor of key prosperity dimensions, particularly environmental quality and sociocultural empowerment. Finally, the level of relationships were quantified to assist destination managers in identifying where to expend effort and resources to improve the implementation of sustainable tourism while considering the key dimensions of prosperity.